2022
DOI: 10.4254/wjh.v14.i6.1120
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis regression following hepatitis C antiviral therapy

Abstract: Hepatitis C virus (HCV) infection is one of the most common causes of liver pathology. It is a major etiological factor of continuous liver injury by triggering an uncontrolled inflammatory response, causing liver fibrosis and cirrhosis. Liver fibrosis is a dynamic process that can be reversible upon timely cessation of the injurious agent, which in cases of HCV is represented by the sustained virological response (SVR) following antiviral therapies. Direct-acting antiviral therapy has recently revolutionized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In line with previous studies, a dynamic reduction of non‐invasive markers of fibrosis was identified in our research. The improvement of liver function might be due to reduced inflammation rather than substantial fibrosis regression 74 ; therefore, its relationship to necroinflammatory improvement cannot be excluded. These data highlight the role of muscle‐liver‐immune crosstalk as a potential pathway implicated in restoring inflammatory response after HCV eradication by DAA.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, a dynamic reduction of non‐invasive markers of fibrosis was identified in our research. The improvement of liver function might be due to reduced inflammation rather than substantial fibrosis regression 74 ; therefore, its relationship to necroinflammatory improvement cannot be excluded. These data highlight the role of muscle‐liver‐immune crosstalk as a potential pathway implicated in restoring inflammatory response after HCV eradication by DAA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also aimed to identify potential predictors of fibrosis decline. Both host factors, such as the presence of liver cirrhosis, old age of the patient, alcohol consumption, diabetes mellitus or BMI, and viral factors (genotype, viral load) were investigated, but the results remained inconclusive [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for post-SVR HCC development include age, male gender, lower baseline albumin, higher bilirubin levels, an FIB-4 score > 3.25, hepatitis B coinfection, and liver stiffness post-SVR ≥ 20 kPa [39]. Some studies have examined the impact of SVR achieved with DAAs on hepatic fibrosis in patients with chronic hepatitis C. These studies found that fibrosis improved by at least one stage in 56% of patients after a 15-month follow-up, and, notably, cirrhosis reversed in 29% of patients [40].…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…It is essential to recognize the potential for fibrosis reversal, particularly in high-risk patients (those with advanced liver fibrosis-F3 or cirrhosis-at the time of DAA treatment). Doing so can lead to improved clinical outcomes, including a reduction in hepatic decompensation and complications, and a decreased risk of HCC development [40].…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%